Perbandingan Akupresure dan Herbal Kunyit Asam Terhadap Dysmenorhea pada Remaja Putri - Mintaningtyas, Sestu Iriami; Iryani, Dwi (Universitas Malahayati, 2025)
ABSTRACT Adolescents are residents in the age range of 10-19 years. The age range of adolescence is divided into three, namely mid-adolescence 15-18 years, late adolescence 18-24 years. Adolescence is a transition period from childhood to adulthood in women, a sign of reproductive organ maturity, namely menstruation, usually begins between the ages of 10-16 years, depending on various factors including Women's Health, nutritional status and body weight. The purpose of this study was to analyze the comparison of Acupressure points Li4, SP 6, ST36 and Herbal turmeric tamarind to reduce the intensity of pain in Dysmenorrhea in Adolescent Girls. This type of research uses the Quasy Experimental research method with the design used, namely the Two Group Pre Test and Post Test design. This study provides treatment in the form of Acupressure points Li4, SP6, ST 36 and Herbal turmeric tamarind to reduce Dysmenorrhea Pain in Adolescent Girls. The sample in this study was Adolescent Girls who experienced dysmenorrhea at SMA Yapis Manokwari Regency as many as 30 respondents who were divided into 2 groups with a sampling technique using purposive sampling. This study conducted an analysis of the menstrual pain scale in adolescent girls before and after being given acupressure intervention at points Li4, SP6, ST36 for 6 days of menstruation and the administration of 250 ml of Turmeric Acid Herbal 2 times a day for 3 days according to the SOP. The research instruments used were the Standard Operating Procedure for the implementation of Acupressure at points Li4, SP6, ST36 and Turmeric Acid Herbal, Questionnaire Sheet, Turmeric Acid Herbal, Olive Oil, Visual Analog Scale (VAS) Scale Sheet. The data analysis method for Univariate analysis was carried out on each variable from the research results to describe each variable from each research result. The data taken were primary data and data analysis used parametric and non-parametric tests. The results of the study obtained from the comparison of acupressure and turmeric and tamarind herbal medicine on dysmenorrhea pain in female adolescents at Yapis High School, Manokwari Regency, showed that in the acupressure and turmeric and tamarind herbal medicine groups before and after treatment, the P-value was <0.05, which means that both groups had an effect on reducing menstrual pain during dysmenorrhea in female adolescents at Yapis High School, Manokwari Regency. Keywords: Acupressure, Turmeric Tamarind Herbs, Dysmenorrhea ABSTRAK Remaja merupakan penduduk dalam rentang usia 10-19 tahun. Rentang waktu usia remaja di bagi tiga yaitu masa remaja pertengahan 15-18 tahun, masa remaja akhir 18-24 tahun. Masa remaja merupakan masa peralihan dari masa kanak-kanak menuju dewasa pada Perempuan tanda kematangan organ reproduksi yaitu menstruasi biasanya dimulai antara usia 10-16 tahun, tergantung pada berbagai faktor termasuk Kesehatan Wanita status nutrisi dan berat tubuh. Tujuan penelitian ini adalah menganalisa perbandingan Akupresure titik Li4, SP 6, ST36 dan Herbal kunyit asam untuk menurunkan intensitas nyeri pada Dysmenorhea pada Remaja Putri. Jenis Penelitian ini menggunakan Metodepenelitian Quasy Eksperimental dengan rancangan yang digunakan yaitu Two Group Pre Test and Post Test design. Penelitian ini memberikan perlakuan berupa Akupresure titik Li4, SP6,ST 36 dan Herbal kunyit asam terhadappenurunan Nyeri Dysmenorhea pada Remaja Putri. Sampel dalam penelitian ini adalah Remaja Putri yang mengalami dysmenorrhea di SMA Yapis Kabupaten Manokwari sebanyak 30 responden yang terbagi 2 kelompok dengan teknik pengambilan sampel menggunakan purposive sampling. Penelitian ini melakukan analisis skala nyeri menstruasi pada remaja putri sebelum dan sesudah diberikan intervensi akupresure titik Li4, SP6, ST36 selama 6 hari menstruasi dan Pemberian Herbal Kunyit Asam sebanyak 250 ml 2 kali per hari lamanya 3 hari sesuai SOP. Instrumen penelitian yang digunakan adalah Standar Operasional Prosedur pelaksanaan Akupresure titik Li4, SP6, ST36 dan Herbal kunyit asam, Lembar Kuesioner, Herbal Kunyit Asam, Minyak Zaitun, Lembar Visual Analog Scale (VAS) Scale. Metode analisis datauntuk analisis Univariat dilakukan pada tiap variabel dari hasil penelitian untuk mendeskripsikan tiap variabel daritiap hasil penelitian. Data yang diambil merupakan data primer dan analisa data menggunakan uji parametrik dan non parametrik test. hasil penelitian yang diperoleh dari perbandingan akupresur dan herbal kunyit asam terhadap nyeri disminore pada remaja putri di SMA Yapis Kabupaten Manokwari mendapatkan hasil bahwa pada kelompok akupresur dan herbal asam kunyit sebelum dan sesudah perlakuan mendapatkan hasil nilai P-value <0.05 yang berarti pada kedua kelompok mempunyai pengaruh menurunkan nyeri saat haid disminore pada remaja putri di SMA Yapis Kabupaten manokwari. Kata Kunci: Akupresure, Herbal Kunyit Asam, Dysmenorhea.